Preparation and Evaluation of Azelaic Acid Topical Microemulsion Formulation: In Vitro and In Vivo Study - Wan-Hsuan Hung; Ping-Kang Chen; Chih-Wun Fang; Ying-Chi Lin; Pao-Chu Wu (MDPI AG, 2021)
The aim of this study was to design oil in water (O/W) microemulsion formulations for the topical administration of azelaic acid. The permeability of azelaic acid through rat skin and the anti-inflammatory activities of the formulations were conducted to examine the efficacy of the designed formulations. Skin irritation and stability tests were also performed. The permeability of azelaic acid was significantly increased by using O/W microemulsions as carriers. The edema index of ear swelling percentage was significantly recovered by the 5% drug-loaded formulation and a 20% commercial product, demonstrating that the experimental formulation possessed comparable effect with the commercial product on the improvement of inflammation. The experimental formulation did not cause significant skin irritation compared to the negative control group. Moreover, the drug-loaded formulation also showed thermodynamic stability and chemical stability after storage for 30 days. In conclusion, the O/W microemulsion was a potential drug delivery carrier for azelaic acid topical application.